American sports - Rader, Benjamin G. (Prentice Hall, 1996)
American Sports offers a reflective, analytical history of American sports from the colonial era to the present. Readers will focus on the diverse relationships between sports and class, gender, race, ethnicity, religion and region, and understand how these interactions can bind diverse groups together. By considering the economic, social and cultural factors that have surrounded competitive sports, readers will understand how sports have reinforced or challenged the values and behaviors of society.